LEGAL PROTECTION FOR CONSUMERS IN E-COMMERCE TRANSACTIONS IN INDONESIA: CONTRACT VALIDITY AND DISPUTE RESOLUTION EFFECTIVENESS - ALAMSYAH, SAKTI; HASIBUAN, FAUZIE YUSUF (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2025)
This study explores consumer protection in Indonesia’s e-commerce transactions, focusing on contract validity and the effectiveness of dispute resolution mechanisms. Standardized contracts in e-commerce often limit consumers' ability to negotiate terms, placing them in a weaker position. Analysis of existing laws, including the Indonesian Civil Code, Consumer Protection Law, and the Electronic Information and Transactions (ITE) Law, indicates that current regulations inadequately protect consumers in digital transactions. Additionally, the role of the Consumer Dispute Settlement Body (BPSK) is assessed, revealing jurisdictional and capacity challenges, especially in cross-border cases. To improve consumer protection, this study recommends regulatory reforms requiring seller verification, accurate product information, enhanced BPSK authority, and improved consumer education. These steps are essential to foster a safer, fairer, and more transparent e-commerce environment in Indonesia, aligning legal protections with the rapid growth of digital commerce.